Impact of roof height non-uniformity on pollutant transport between a street canyon and intersections - Nosek, Štěpán; Kukačka, Libor; Jurčáková, Klára; Kellnerová, Radka; Jaňour, Zbyněk (Environmental pollution (1987), 2017)
This paper presents an extension of our previous wind-tunnel study (Nosek et al., 2016) in which we highlighted the need for investigation of the removal mechanisms of traffic pollution from all openings of a 3D street canyon. The extension represents the pollution flux (turbulent and advective) measurements at the lateral openings of three different 3D street canyons for the winds perpendicular and oblique to the along-canyon axis. The pollution was simulated by emitting a passive gas (ethane) from a homogeneous ground-level line source positioned along the centreline of the investigated street canyons. The street canyons were formed by courtyard-type buildings of two different regular urban-array models. The first model has a uniform building roof height, while the second model has a non-uniform roof height along each building's wall. The mean flow and concentration fields at the canyons' lateral openings confirm the findings of other studies that the buildings' roof-height variability at the intersections plays an important role in the dispersion of the traffic pollutants within the canyons. For the perpendicular wind, the non-uniform roof-height canyon appreciably removes or entrains the pollutant through its lateral openings, contrary to the uniform canyon, where the pollutant was removed primarily through the top. The analysis of the turbulent mass transport revealed that the coherent flow structures of the lateral momentum transport correlate with the ventilation processes at the lateral openings of all studied canyons. These flow structures coincide at the same areas and hence simultaneously transport the pollutant in opposite directions.
Keywords: velkoměsta; Wind; Cities; teoretické modely; vítr; Vehicle Emissions; látky znečišťující vzduch; výfukové emise vozidel; Air Pollutants; Models, Theoretical